THE EVOLVING LANDSCAPE OF EDUCATION: CHALLENGES AND INNOVATIONS - Achilova Dilnora Salijanovna (Journals Park Publishing, 2024)
Education, a cornerstone of societal development, has undergone significant transformations over the past few decades. The rapid advancement of technology shifts in pedagogical approaches, and the increasing emphasis on inclusivity and lifelong learning are reshaping the educational landscape. This article explores the current state of education, the challenges it faces, and the innovative solutions that are emerging to address these issues.
Keywords: Education, access to education, educational equity, quality of education, technological integration, personalized learning, project-based learning, blended learning, social-emotional learning, educational innovations, digital divide, lifelong learning, pedagogical approaches, inclusive education.